Prefactibilidad de un sistema solar fotovoltaica para uso alternativo de energización en la subregión alta del departamento de La Guajira (2021)
This degree project talks about the pre-feasibility of a photovoltaic solar system for alternative energy use in the upper subregion of the department of La Guajira, which serves the development processes of the communities. This pre-feasibility is analyzed with respect to the alternative most used in the area, such as diesel plants. The project recognizes basic subsistence consumption, solar irradiance conditions, alternative energy policies in Colombia and the financial study of the photovoltaic system.The research was carried out under the modality of qualitative and quantitative design